Opium as a carcinogen: A systematic review and meta-analysis - Mohammad Zamiri Bidary; Mehrdad Sahranavard; Arash Akhavan Rezayat; Alireza Omranzadeh; Seyyed Hasan Hoseiny; Ali Kabirian; Amirhossein Sahebkar (EClinicalMedicine, 2021)
Background: Opium and its pyrolysates have been investigated as potential carcinogenic material through several studies in different body systems; however, the results were controversial and no consensus was achieved with this regard. Thus, we aimed to systematically review and meta-analyze all existed evidence regarding association between opium consumption and cancer. Methods: Four major electronic databases including ISI Web of Science, PubMed, Scopus, and Embase along with Magiran and SID were searched thoroughly for all published articles from inception up to September 25, 2020. All studies were appraised critically by Newcastle Ottawa Scale (NOS) checklist. Relevant demographic data and the intended results of the selected studies were extracted and their Odds ratios (OR) were pooled using Comprehensive Meta-analysis (CMA). The cumulative risk of opium for developing different cancers was calculated. Findings: 34 studies comprised of 18,230 individuals were entered in our systematic review and finally 32 publications were enrolled in meta-analysis. Overall, using the random effects model, opium consumption was associated with increased rate of malignancies in both minimally[OR = 4.14 95%CI = (3.32–5.15)] and fully adjusted [OR = 4.35 95%CI = (3.36–5.62)] analyses. Moreover, using random effects fully adjusted model, the subgroup analysis revealed increased risk for larynx [OR = 9.58 95%CI = (6.31–14.53)], respiratory [OR = 9.02 95%CI = (6.27–12.96)], head and neck [OR = 8•03 95%CI = (4.03–16.00)], and colon [OR=5.58 95%CI = (3.14–9.92)] cancers for opium consumers compared to non-consumers. Interpretation: Opium consumption is highly associated with all reported types of cancers, especially in fully adjusted model; however, basic pathophysiology should be further investigated. Funding: None.